2022
DOI: 10.3389/fpsyg.2022.918045
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of decisional and emotional forgiveness on distress and well-being: A three-wave study of Indonesian adults

Abstract: Research suggests that interpersonal forgiveness is beneficial to individual functioning, but few longitudinal studies have explored the independent contributions of decisional and emotional forgiveness to reducing different forms of distress and improving multidimensional well-being. In this three-wave (T1: December 2020; T2: January 2021; T3: February 2021) prospective study of predominantly young Indonesian adults (n = 595), we examined the associations of decisional and emotional forgiveness with three ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, a comparative scientific study, predominantly on young 585 Indonesian adults suggests that in a collectivistic cultural context such as Indonesia, restorative forgiveness (decisional forgiveness) following a transgression, where a decision is made to forgive, rather than seeking retribution or holding grudges may offer greater short-term benefits for well-being compared to emotional forgiveness (Cook et al, 2022). Another research was done by (Suhron et al, 2020) on 52 schizophrenia patients with violent behavior with a sampling technique.…”
Section: Emotional Forgiveness and Forgiveness Therapymentioning
confidence: 99%
“…On the other hand, a comparative scientific study, predominantly on young 585 Indonesian adults suggests that in a collectivistic cultural context such as Indonesia, restorative forgiveness (decisional forgiveness) following a transgression, where a decision is made to forgive, rather than seeking retribution or holding grudges may offer greater short-term benefits for well-being compared to emotional forgiveness (Cook et al, 2022). Another research was done by (Suhron et al, 2020) on 52 schizophrenia patients with violent behavior with a sampling technique.…”
Section: Emotional Forgiveness and Forgiveness Therapymentioning
confidence: 99%
“…As these brief examples indicate, forgiveness is a highly individual experience that cannot be reduced to a generalized “forgiveness process” (Z. J. Chen et al, in press; Cook et al, 2022; Cowden, Chen, et al, 2023).…”
Section: Forgiveness Is Experienced Heterogeneouslymentioning
confidence: 99%
“…Recognizing that there are opportunities to improve our understanding of forgiveness and its implications for health and well-being by employing rigorous analytic approaches to study forgiveness from a whole person perspective, a growing number of longitudinal studies have reported on the associations of forgiveness with numerous outcomes across many domains of individual functioning (e.g., Y. Chen et al, 2019; Cook et al, 2022; Cowden, Chen, et al, 2023; Long et al, 2020). The findings reported in such studies—though mostly pertaining to the subjectivity that characterizes well-being—have corroborated, challenged, and extended prior research on forgiveness and its connection to health and well-being, with evidence across these studies generally supporting stronger and more consistent associations with psychosocial outcomes.…”
Section: Forgiveness Is Related To Whole Person Functioningmentioning
confidence: 99%
“…Still, virtually all research on self‐forgiveness has taken place in Western countries (Sandage et al, 2020). A common dimension on which cultures are thought to differ is individualism–collectivism, which can shape one's understanding and experience of interpersonal forgiveness and perhaps self‐forgiveness as well (Cook et al, 2022; Hook et al, 2009; Sandage et al, 2020). To achieve a more comprehensive understanding of the linkages between self‐forgiveness and well‐being, additional research is needed in non‐Western, predominantly collectivistic contexts.…”
Section: Hypothesesmentioning
confidence: 99%